Application of Character Education for Children with Special Needs in Special Schools of Perwari Padang - Firunika Intan Cahyani; Eko Purnomo; Eddy Marheni (Fakultas Ilmu Pendidikan)
Children with special needs have problems with low social character and personal character. The purpose of this study is to find out the implementation of character education in children with special needs. This research is a qualitative research,This research was conducted on August 2 to September 29, 2018 at Special Schools of Perwari Padang, West Sumatra. The informants in this study were teachers who taught at the extraordinary Perwari Padang school which amounted to 5 people, with the object of research totaling 64 students special needs. Data collection methods use observation, documentation, interviews. The findings of the researcher indicate several behavioral problems which indicate that there is no personal character or social character in children with special needs (especially for mentally retarded children). The results of the study show the importance of applying the values of character education to children with special needs for the realization of a better national character.